From Control to Empowerment: Explaining the Mechanisms of Regulatory Slippage and the Conditions for Its Restraint in Digital Parenting - Bechka, Samah (Journal of Ecohumanism, 2025)
This digital paper aims to analyze the phenomenon of “control slippage” in digital parenting practices through an integrated analytical framework that combines the perspectives of family psychology, affordance theory, self-determination theory, and the media affordance model. It adopts a three-level analytical methodology (individual, interactive, systemic) to examine the underlying mechanisms behind the transformation of digital tools from preventive means into instruments of psychological control within family dynamics.The results reveal that “control slippage” represents a form of boundary disturbance in family relationships, where the interaction between the technological affordances of digital platforms and the frustration of basic psychological needs (autonomy, competence, relatedness) generates a self-reinforcing slippage loop. The paper also proposes a transformative model based on four “inhibition conditions”: (digital contract, periodic reviews, reasonable reciprocity, and gradual withdrawal) to achieve balance in digital parenting practices between the demands of protection and the needs of psychological growth. Thus, this research paper provides both a theoretical contribution and a field-oriented project for establishing the emerging discipline of digital family psychology, aiming to shift digital practices from surveillance to empowerment.